Omo onile and Violence in Real Estate Development in Lagos, Nigeria. Issue 2 (3rd July 2017) - Ayodele, Johnson
ABSTRACT: This study examines the influence of omo onile (literally meaning "the child of the landowner") on real estate development in Lagos, Nigeria. the land sale-associated violence is one significant challenge to estate development in Lagos. Quantitative and qualitative data were collected, which were analysed at three levels, and content analysed respectively. Logistic regression results indicated that respondents who admitted that omo onile had a negative impact on real estate were five times more likely to disengage in real estate investment, relative to those who noted no significant effects. The study concludes that unfair access to land adversely impacts on real estate development. therefore, the government should dismantle legislative impediments, control omo onile and strengthen community frameworks for access to land in Lagos.